Contributions of Dexter French (1918–1981) to cycloamylose/cyclodextrin and starch science. (1st April 2021) - Crini, Grégorio; French, Alfred D.; Kainuma, Keiji; Jane, Jay-lin; Szente, Lajos
Highlights: Professor French was an eminent scientist in the field of carbohydrates and related enzymes. A comprehensive review on Professor French's scientific works is presented. In 1942, Professor French introduced the cycloamylose nomenclature. In the 1950s, Professor French made outstanding contributions on cyclodextrin chemistry. Professor French proposed the double helical structure for native starch in 1972. Abstract: Professor Dexter French (1918–1981) was an American chemist and biochemist at Iowa State College (University in 1959). He devoted his career to advance knowledge of polysaccharides and oligosaccharides, in particular starch, cyclodextrins, and enzymes. Cyclodextrins are oligosaccharides obtained from starch and are typically cage molecules with a hydrophobic cavity that can encapsulate other compounds nowadays the basis for many industrial applications. Since the 1960s, he has been recognized as an outstanding authority in the field of starches and cyclodextrins and has inspired researchers in laboratories around the world. This review, on the fortieth anniversary of his death, commemorates his remarkable contribution to starch and cyclodextrin chemistry. Firstly, we give an overview of his personal life and career. Secondly, we highlight some of the results on starch and cyclodextrins from Professor French and his group. A third part discusses his impact on the modern chemistry of cyclodextrins and starch.